A computational fluid dynamics simulation of oil-air flow between the cage and inner race of an aero-engine bearing - Adeniyi, Akinola A.; Morvan, Herve; Simmons, Kathy (American Society of Mechanical Engineers, 2017)
In aero-engines, the shafts are supported on bearings that carry the radial and axial loads. A ball bearing is made up of an inner race, an outer race, and a cage, which contains the balls, these together comprise the bearing elements. The bearings require oil for lubrication and cooling. The design of the bearing studied in this work is such that the oil is fed to the bearing through holes/slots in the inner race. At each axial feed location, the oil is fed through a number of equispaced feedholes/slots but there are a different number of holes at each location. Once the oil has passed through the bearing, it sheds outward from both sides into compartments known as the bearing chambers. A number of studies have been carried out on the dynamics of bearings. Most of the analyses consider the contributions of fluid forces as small relative to the interaction of the bearing elements. One of the most sophisticated models for a cage-raceway analysis is based on the work of Ashmore et al. (2003, "Hydrodynamic Support and Dynamic Response for an Inner-Piloted Bearing Cage" Proc. Inst. Mech. Eng. Part G, 217, pp. 19-28], where the cage-raceway is considered to be a short journal bearing divided into sectors by the oil feeds. It is further assumed that the oil exits from the holes and forms a continuous block of oil that exits outward on both sides of the cage-raceway. In the model, the Reynolds equation is used to estimate the oil dynamics. Of interest in this current work is the behavior of the oil and air within the space bounded by the cage and inner race. The aim is to determine whether oil feed to the bearing can be modeled as coming from a continuous slot or if the discrete entry points must be modeled. A volume of fluid (VOF) computational fluid dynamics (CFD) approach is applied. A sector of a ball bearing is modeled with a fine mesh, and the detailed simulations show the flow behavior for different oil splits to the three feed locations of the bearing, thus providing information useful to understanding oil shedding into the bearing chambers. This work shows that different flow behaviors are predicted by models where the oil inlets through a continuous slot are compared to discrete entry holes. The form and speed of oil shedding from the bearing are found to depend strongly on shaft speed with the shedding speed being slightly higher than the cage linear speed. The break-up pattern of oil on the cage inner surface suggests that smaller droplets will be shed at higher shaft speed.